The gaseous halo of the Milky Way - Marasco, Antonino <1984> (Alma Mater Studiorum - Università di Bologna, 2013)
In the last decade, sensitive observations have revealed that disc galaxies are surrounded by multiphase gaseous halos produced by the circulation of gas from the discs to the environment and vice-versa. This Thesis is a study of the gaseous halo of the Milky Way carried out via the modelling of the HI emission and the available absorption-line data. We fitted simple kinematical models to the HI LAB Survey and found that the Galaxy has a massive (~3x10^8 Mo) HI halo extending a few kiloparsecs above the plane. This layer rotates more slowly than the disc and shows a global inflow motion, a kinematics similar to that observed in the HI halos of nearby galaxies. We built a dynamical model of the galactic fountain to reproduce the properties of this layer. In this model, fountain clouds are ejected from the disc by SN feedback and - as suggested by hydrodynamical simulations - triggers the cooling of coronal gas, which is entrained by the cloud wakes and accretes onto the disc when the clouds fall back. For a proper choice of the parameters, the model reproduces well the HI data and predicts an accretion of coronal gas onto the disc at a rate of 2 Mo/yr. We extended this model to the warm-hot component of the halo, showing that most of the ion absorption features observed towards background sources are consistent with being produced in the turbulent wakes that lag behind the fountain clouds. Specifically, the column densities, positions, and velocities of the absorbers are well reproduced by our model. Finally, we studied the gas content of galaxies extracted from a cosmological N-body+SPH simulation, and found that an HI halo with the forementioned properties is not observed, probably due ti the relatively low resolution of the simulations.